Poszukiwanie panoram - Ławniczak, Grażyna (My University, 1994)
Obraz panoramowy powstał w końcu XVIII wieku, jako nowość techniczno – przyrodnicza, miał zbliżać widzów do natury. Przy pomocy środków plastycznych osiągano iluzję pewnej rzeczywistości, wyobrażano sceny historyczne, rozegrane bitwy, widoki miast i naturalne krajobrazy. Olbrzymie płótna panoramowe, rozpięte w kole, miały standardowe wymiary 15 x 120 m. Malarstwo panoram zainteresowało również polskich artystów. Wojciech Kossak (1856-1942) i Jan Styka (1858-1925) namalowali pierwszą polską panoramę "Bitwa pod Racławicami" w setną rocznicę insurekcji kościuszkowskiej, prezentowana była podczas Powszechnej Wystawy Krajowej (1894) we Lwowie. Zamieszczone w repozytorium artykuły krótko ujmują historię polskich panoram, ukazały się w czasopiśmie "Spotkania z Zabytkami" (1994-1995). Zostały napisane w oparciu o materiały zebrane w związku z wystawą poświęconą polskim panoramom, jaka miała miejsce w Bibliotece Uniwersyteckiej w Poznaniu (styczeń – maj 1990). Była to prezentacja albumów, przewodników z wystaw panoram sprzed wieku, pocztówek, które zachowały się w bibliotekach polskich, zawierają one najczęściej opis i reprodukcje obrazu.

Panoramic paintings became immensely popular at the end of the eighteenth century and were seen as a novelty that combined technology with traditional representation of nature. The designed purpose of these massive artworks was to bring viewers closer to nature. With different artistic means of expression and visual results it was possible to provide an illusion of reality – of historical and battlefield scenes, cityscapes and natural landscapes. The standard dimensions of these gigantic canvases, stretched in a circle, were usually 15 x 120 m. Just like everywhere else, artists in Poland were also interested in panoramic painting. Wojciech Kossak (1856-1942) and Jan Styka (1858-1925) were the first Polish artists who painted the first Polish panoramic painting – the Racławice Panorama. The Panorama was to honour the hundred anniversary of the Kosciusko Insurrection and was presented during the Polish General Exhibition in Lwow in 1894. The present articles submitted to the institutional repository briefly describe the history of Polish panoramas and were originally published in the journal "Spotkania z Zabytkami" between 1994-1995. Both articles are based on the materials collected in connection with the exhibition devoted to Polish panoramas staged at Poznań University Library in January – May 1990. The exhibition featured picture books and leaflets that accompanied the exhibitions of panoramic paintings that had been preserved in libraries in Poland and most frequently included descriptions and images of the presented panoramas.
Keywords: malarstwo polskie; Polish paintings; obrazy panoramowe; panoramic paintings; cineramy; cycloramic paintings; wystawy sztuki i gospodarcze; art and economic exhibitions; pamiątki narodowe; national heritage items